The Impact of Synchronous Telehealth Services With a Digital Platform on Day-by-Day Home Blood Pressure Variability in Patients with Cardiovascular Diseases: Retrospective Cohort Study - Ying-Hsien Chen; Chi-Sheng Hung; Ching-Chang Huang; Jen-Kuang Lee; Jiun-Yu Yu; Yi-Lwun Ho (JMIR Publications, 2022)
BackgroundHypertension is associated with a large global disease burden with variable control rates across different regions and races. Telehealth has recently emerged as a health care strategy for managing chronic diseases, but there are few reports regarding the effects of synchronous telehealth services on home blood pressure (BP) control and variability. ObjectiveThe objective of this study is to investigate the effect of synchronous telehealth services with a digital platform on home BP. MethodsThis retrospective study was conducted by the Taiwan ELEctroHEALTH study group at the Telehealth Center of the National Taiwan University Hospital. We analyzed home BP data taken from 2888 patients with cardiovascular disease (CVD) enrolled in our telehealth program between 2009 to 2017. Of the 2888 patients with CVD, 348 (12.05%) patients who received home BP surveillance for ≥56 days were selected for BP analysis. Patients were stratified into three groups: (1) poorly controlled hypertension, (2) well-controlled hypertension, and (3) nonhypertension. The mean, SD, coefficient of variation (CV), and average real variability were calculated. ResultsTelehealth interventions significantly and steadily reduced systolic blood pressure (SBP) in the poorly controlled hypertension group from 144.8.2±9.2 to 133.7±10.2 mmHg after 2 months (P<.001). BP variability reduced in all patients: SBP-SD decreased from 7.8±3.4 to 7.3±3.4 after 2 months (P=.004), and SBP-CV decreased from 6.3±2.5 to 5.9±2.6 after 2 months (P=.004). Event-free survival (admission) analysis stratified by SBP-SD showed longer time to first hospitalization for Q1 patients compared with Q4 patients (P=.02, odds ratio 2.15, 95% CI 1.18-3.89). ConclusionsSynchronous telehealth intervention may improve home BP control and decrease day-by-day home BP variability in patients with CVD.